ANALISIS KEBANGKRUTAN MENGGUNAKAN METODE SPRINGATE (STUDI KASUS PADA PT. GARUDA INDONESIA, Tbk TAHUN 2018-2020) - Bandi, Maulida Hirdianti; Nurmalina, Radna; Hayatie, Marliza Noor (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
Bankruptcy is a condition of a company that is unable to pay its debts or also a condition that initially the company can operate and then fails in managing its business. Bankruptcy is a condition when a company experiences insufficient funds to run its business. The purpose of this study was to determine the factors that led to bankruptcy at PT. Garuda Indonesia. This study uses the Springate method with the bankruptcy formula. Based on the results of this study, it shows that the company has the potential to go bankrupt because in 2018-2020 its current assets are quite low so that the company does not have the ability to pay its debts. Companies need to take firm, straightforward and appropriate action to address efficiency in operating costs. Then, an inappropriate business strategy is also a factor that causes losses and also human resources who have a poor vision and mission of the company